New cation-mediated enantioselective transformations and catalytic enantioselective photocyclization - Jones, BA (2021)
This thesis describes the development of novel catalytic enantioselective reactions. Chapter 1 describes the development of transformations mediated by chiral ammonium salts. The historical context of enantioselective phase transfer catalysis is provided and the key fundamental advances are detailed. The development of a cation-mediated kinetic resolution of atropisomeric biaryls is described as well as the synthesis and resolution of a range of substituted BINOLs.